Lucho Herrera contribution of sports cycling in Colombia - Troncoso, Leandro Dri Manfiolete [UNESP]; Rondon, Kevin Daniel Rozo; Munoz, Jorge Andrés Jimenez [UNESP]; Robles, Sandra Soledad Troncoso (Federacion Espanola de Asociaciones de Docentes de Educacion Fisica (FEADEF), 2022)
The objective of this article is to understand the contribution of the life experience of professional cyclist Luis Alberto «Lucho» Herrera Herrera to sports cycling in Colombia. Based on the concept of «Pedaling for Citizenship» in the context of an investigation on the cycloactivist movement in South American territory, the methodological procedures used were the semi-structured interview technique for data collection and the phenomenological approach for discursive analysis. The units of meaning emerged: 1) life history with the bicycle; 2) athletic preparation; 3) training structure; 4) conditions for sports training; 5) social values; 6) neocolonialism in South American sports; 7) health when pedaling; 8) promotion of biciculture by public institutions. We conclude that the sports culture of cycling must be linked to the need to formulate political-institutional strategies that promote bi-culture.
La contribución de Lucho Herrera para el ciclismo deportivo en Colombia
Keywords: Bicycling; Citizenship; Cycling; Public policy; Sports